An extensive late Cenozoic terrestrial record of multiple glaciations preserved in the Tintina Trench of west-central Yukon: stratigraphy, paleomagnetism, palesols, and pollen - Duk-Rodkin, Alejandra; Barendregt, René W.; White, James M (NRC Research Press, 2010)
Sherpa Romeo Green journal (pre or post print only) The Tintina Trench in west-central Yukon is a late Miocene graben formed along the antecedent early Tertiary Tintina fault. Since its formation the trench has served as a sediment trap for alluvial and glacial deposits. An extensive record of preglacial, glacial, and interglacial sediments spanning the late Pliocene to late Pleistocene has been preserved and is exposed today in modern landslide scars. This sedimentary record comprises multiple sequences of tills, outwash, mudflows, loess, and paleosols. The glacial sediments are the product of both local (montane) and regional (Cordilleran) ice advances that channeled into the trench, while loess and well-developed paleosols (brunisols and luvisols) reflect nonglacial and interglacial conditions, respectively. The Tintina Trench exposures provide the most complete record of glaciations for the region. Paleomagnetism, paleosols, and palynology provide age constraints for the geological events. A formal stratigraphic nomenclature is proposed for this region. The name West Tintina Trench Allogroup is assigned to the glacial–interglacial and nonglacial strata that occurs above a major regional Miocene–Pliocene unconformity. The allogroup spans the late Pliocene (3.6 Ma) to middle Pleistocene (0.126 Ma), based on magnetostratigraphy and pollen data. The sequence includes an alluvial deposit at the base, overlain by an extensive sequence of tills and outwash, and capped by loess. Paleosols and weathering horizons occur throughout the sequence. Tintina Trench; Beringia; glacial chronology; magnetostratigraphy; early and middle Pleistocene; Yukon paleoenvironments; Yukon paleosols; Yukon pollen; North American glaciations; West Tintina Trench Allogroup. Yes